Astrocyte sodium signaling and the regulation of neurotransmission. Issue 10 (14th November 2015) - Kirischuk, Sergei; Héja, László; Kardos, Julianna; Billups, Brian
Abstract : The transmembrane Na + concentration gradient is an important source of energy required not only to enable the generation of action potentials in excitable cells, but also for various transmembrane transporters both in excitable and non‐excitable cells, like astrocytes. One of the vital functions of astrocytes in the central nervous system (CNS) is to regulate neurotransmitter concentrations in the extracellular space. Most neurotransmitters in the CNS are removed from the extracellular space by Na + ‐dependent neurotransmitter transporters (NeuTs) expressed both in neurons and astrocytes. Neuronal NeuTs control mainly phasic synaptic transmission, i.e., synaptically induced transient postsynaptic potentials, while astrocytic NeuTs contribute to the termination of phasic neurotransmission and modulate the tonic tone, i.e., the long‐lasting activation of extrasynaptic receptors by neurotransmitter that has diffused out of the synaptic cleft. Consequently, local intracellular Na + ([Na + ]i ) transients occurring in astrocytes, for example via the activation of ionotropic neurotransmitter receptors, can affect the driving force for neurotransmitter uptake, in turn modulating the spatio‐temporal profiles of neurotransmitter levels in the extracellular space. As some NeuTs are close to thermodynamic equilibrium under resting conditions, an increase in astrocytic [Na + ]i can stimulate the direct release of neurotransmitter via NeuT reversal. In this review we discuss the role of astrocytic [Na + ]i changes in the regulation of uptake/release of neurotransmitters. It is emphasized that an activation of one neurotransmitter system, including either its ionotropic receptor or Na + ‐coupled co‐transporter, can strongly influence, or even reverse, other Na + ‐dependent NeuTs, with potentially significant consequences for neuronal communication. GLIA 2016;64:1655–1666 Main Points: Activation of neurotransmitter transporters (NeuTs) on astrocytes causes a [Na + ] rise. This sodium signal alters the driving force of other NeuTs. Substantial [Na + ] rises can reverse NeuTs, stimulating the release of gliotransmitters.